Copeptin is increased in resistant hypertension. Issue 12 (December 2016) - Mendes, Margarida; Dubourg, Julie; Blanchard, Anne; Bergerot, Damien; Courand, Pierre-Yves; Forni, Valentina; Frank, Michael; Bobrie, Guillaume; Menard, Joel; Azizi, Michel
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: The participation of vasopressin in the mechanisms of resistant hypertension is unclear. We compared plasma copeptin concentration, a surrogate marker for vasopressin secretion, between patients with resistant hypertension and those with controlled blood pressure (CBP), in a post hoc analysis of the Prise en charge de l'Hypertension Artérielle RESistante au traitement trial. Methods: After 4-week treatment with irbesartan 300 mg/day, hydrochlorothiazide 12.5 mg/day, and amlodipine 5 mg/day (baseline), 166 patients were classified as having resistant hypertension ( n = 140) or CBP ( n = 26) by ambulatory BP monitoring. Patients with resistant hypertension were then randomized for 12 weeks of sequential nephron blockade ( n = 74) or sequential renin–angiotensin system blockade ( n = 66). Plasma copeptin concentration was measured at baseline and week 12 by immunoassay. Results: Baseline plasma copeptin concentration was positively associated with male sex, plasma osmolality, BP, and negatively with glomerular filtration rate. It was higher in the resistant hypertension than in the CBP group [geometric mean 5.7 (confidence interval 95% 5.1–6.4) vs. 2.9 (2.3–3.9) fmol/ml, adjusted P < 0.0001). The relationship between plasma copeptin concentration and urinary osmolality was similar in the two groups. At 12 weeks, plasma copeptin concentration in patients whose BP was controlled by sequential nephron blockade or sequential renin–angiotensin system blockade [6.8 (5.6–8.2) and 4.3 (3.0–5.9) fmol/ml, respectively) remained significantly higher than in patients with CBP at baseline ( P < 0.0001 vs. both). Conclusion: In patients with resistant hypertension, plasma copeptin concentrations were approximately two-fold higher than those of patients with CBP, after adjustment for plasma osmolality. This difference was not accounted for by renal resistance to vasopressin, suggesting a primary reset of osmostat.